2019
DOI: 10.1111/ijcp.13450
|View full text |Cite
|
Sign up to set email alerts
|

Systolic blood pressure trajectory and cardiovascular outcomes: An analysis using data in the Systolic Blood Pressure Intervention Trial

Abstract: Background Blood pressure changes in response to medication intensification differ over time across individuals, and could affect their cardiovascular outcomes. We aimed to investigate the relationship between systolic blood pressure (SBP) trajectory and cardiovascular outcomes using data from the Systolic Blood Pressure Intervention Trial (SPRINT). Methods Groups of SBP trajectory were modelled separately in the standard and intensive treatment groups. SBP at each site visit post randomisation were used for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…BP trajectory is helpful for capturing the dynamic change of BP within a certain period and visualizing the direction and size of BP variability. Recent longitudinal studies suggest that subgroups with distinct trajectories of BP change may be associated with a variety of clinical outcomes such as cardiovascular events [ 15 18 ], stroke [ 18 , 19 ], and all-cause mortality [ 17 , 18 , 20 ]. Given the close association between the cardiovascular and cerebrovascular burden and dementia [ 21 , 22 ], we hypothesized that BP trajectory patterns would have predictive significance for the risk of subsequent dementia outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…BP trajectory is helpful for capturing the dynamic change of BP within a certain period and visualizing the direction and size of BP variability. Recent longitudinal studies suggest that subgroups with distinct trajectories of BP change may be associated with a variety of clinical outcomes such as cardiovascular events [ 15 18 ], stroke [ 18 , 19 ], and all-cause mortality [ 17 , 18 , 20 ]. Given the close association between the cardiovascular and cerebrovascular burden and dementia [ 21 , 22 ], we hypothesized that BP trajectory patterns would have predictive significance for the risk of subsequent dementia outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The number of patients in each trajectory group was set to exceed 3% of the study population. 21 , 22 The models were fitted using the SAS ProcTraj procedure. 21 Finally, four distinct HbA1c trajectories were identified in both of the standard and intensive treatment arms ( Figure 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Power calculations were performed for the primary outcome variable, i.e., the between groups difference in systolic blood pressure. This showed that a total sample size of 45 will be necessary to provide 80% power to detect a minimally important clinical difference (MCID) of 6 mmHg between groups [ 40 ], with a projected standard deviation of 5.5 mmHg in each group [ 41 ], accounting for a loss to follow up rate of 10%.…”
Section: Methodsmentioning
confidence: 99%